THE RELEVANCE OF VOCATIONAL SCHOOL CURRICULUM TO THE INDUSTRIAL WORLD DEMANDS: PERCEPTION OF ACCOUNTING TEACHERS OF VOCATIONAL SCHOOLS IN SLEMAN - Ananda Normalita Putri; Ani Widayati (Jurnal Pendidikan Akuntansi Indonesia, 2020)
This research discusses the vocational school majoring in accounting about the relevance of the vocational school curriculum to the demands of the Industrial Business World. This research is quantitative descriptive research. The analysis technique used is descriptive analysis with a percentage. The results of this research indicate that: (1) Accounting Vocational Teachers in Sleman Regency are very good at knowing the needs of the industrial world of business. (2) Perception of Vocational School Teachers in Accounting in Sleman Regency on the Curriculum Relevance seen from (a) The objectives of the Vocational Accounting curriculum used so far are already relevant to Industrial Business World requests. (b) The accounting learning materials at the Vocational School used so far are already relevant to the Industrial Business World requests.